Egypt’s Takaful and Karama cash transfer program: Evaluation of program impacts and recommendations - Breisinger, Clemens; ElDidi, Hagar; El-Enbaby, Hoda; Gilligan, Daniel O.; Karachiwalla, Naureen; Kassim, Yumna; Kurdi, Sikandra; Jilani, Amir Hamza; Thai, Giang (International Food Policy Research Institute, 2018)
Egypt has been providing cash to poor households through its first conditional cash transfer program, Takaful and Karama, a social protection program run by the Ministry of Social Solidarity (MoSS), since March 2015. Takaful (“Solidarity”) supports poor families with children under 18, while Karama (“Dignity”) supports the elderly poor and people living with disabilities. The cash transfer program has enrolled 2.25 million families across all of Egypt’s governorates. The amount of the Takaful cash transfer provided to households depends on the number of children and their school level. The Karama program provides a set amount per individual. In order to reach the poorest households, participants are selected using a proxy means test. In the Takaful program, 89 percent of recipients are women, while only 11 percent are men. Beginning in 2018, Takaful will also begin implementing conditionalities, requiring households in the program to ensure their children attend school and participate in health screenings, added to antenatal care for pregnant women and post-natal care. The Takaful and Karama program was evaluated by the International Food Policy Research Institute (IFPRI) using both quantitative statistical methods (simple questions asked to many households during a survey) and qualitative methods (more in-depth questions asked to fewer households in longer interviews). The evaluation was designed to measure and explain the impacts of the cash transfers on household welfare, and to examine whether the program’s criteria for household selection were effective in identifying poor households. This brief, which focuses on the Takaful component of the program, summarizes the main findings from the evaluation and key recommendations.